(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In the Indian modern country is fast emerging as a global power but for half of its population, the women across the country, struggle to live life with dignity continues. Women, irrespective of their class, caste and educational status, are not safe In the modern society women have been the victims of exploitations since long time in different fields in their life both physically, socially, mentally and economically. There are several causes of sexual as well as moral abuse which are very often highlighted by the media in Indian modern society, and a lot of those also remain unexplored. Although, such violence against women, sexual harassment, exploitation to women is not of recent origin, its trace is found in the history of ancient India. Women are facing problems in every sphere of life whether employment, access to health care or property rights. India is fast developing but women’s in India continue to be discriminated. The declining sex ratio in India amply portrays the discrimination shown towards women at the stage of birth. They are victims of crime directed specifically at them, rape, kidnapping and abduction, dowry-related crimes, molestation, sexual harassment, eve-teasing, etc. It is realized that the long run supremacy of male over female in all respect in the patriarchal society in India is highly responsible for arresting the empowerment of women. women are being trafficked for sex, harassment at workplaces and tortured in family and society. The paper has attempted to find out the Indian perspectives women exploitation in modern society.